Natural food monitoring of Sumatran elephant (Elephas maximus sumatraensis) in Taman Hutan Raya Cut Nya’ Dhien Seulawah, Aceh Besar - DJUFRI DJUFRI (Biodiversitas Journal of Biological Diversity, 2003)
The objectives of this research were to monitoring natural food of Sumatran elephant; determine rank taxonomy of species,and to give information quantitative value of taxa for vegetation analysis. The wide of area total Taman Hutan Raya Cut Nya’ Dhien Seulawah were 6.220 Ha. About 20% of area total used as an observed area. The data was collected bytransect and quadratic plot method. The observed area it was took 10 transect with 500 m of long for observed station.Each observed station was put seven and ten plot samples systematically. Each plot samples has a 5 m2 of width. Theresult indicated that there were 69 species of the plant including 23 families. Diversity index was between 1.9838-2.7202;an evenness index was between 1.6868-2.0631. The importance value is relatively low on all station observed. The refer of importance value show that Oplismenus burmanii, Imperata cylindrica, Crassocephalum crepidiodes, Mimosa pudica, and Zingiber aquosum were dominated on secondary forest and Zingiber zerumbet, Zingiber purpureum, and Oplismenus burmanii were dominated on primary forest. The result of diversity index show that regeneration of natural food in Taman Hutan Raya Cut Nya’ Dhien Seulawah is available constant because grazing occurred with continue by elephant.© 2003 Jurusan Biologi FMIPA UNS SurakartaKey words: elephant, Taman Hutan Raya, importance value, diversity index.